Blended Learning for Medical First Responder Training: Needs Analysis - Herlinawati, Herlinawati; Tarjiah, Indina; Wirasti, Murti Kusuma (Universitas Pendidikan Ganesha, 2021)
The rapid development of technology demands a fast, easy, cheap, effective, and efficient system and can be accessed anytime and anywhere, including education and training. In the world of education, technological progress is marked by the number of people using the blended learning model. This study aims to obtain and collect information, data, and opinions from stakeholders and training participants at the Training Center of National Search and Rescue Agency to develop a blended learning model for Medical First Responder Training for responders. This study uses the Research and Development (RnD) method with the Integrative Learning Design Framework development model and the PEDATI development strategy. This research is limited only to the initial analysis stage, namely in the form of field studies and literature studies to determine the needs of the Medical First Responders Education and Training and the needs of students who will be the first steps in developing blended learning of MFR training for rescuers within the National Search and Rescue Agency. This study indicates that the National Search and Relief Education and Training Center needs an effective and efficient learning model, coupled with the training participants' responses indicating that they wish to have alternative learning sources. The results of this need analysis research can serve as the basis for the development of blended learning training in Medical First Responder.